2017
DOI: 10.1104/pp.17.00098
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Interplay between LEAFY and APETALA1/CAULIFLOWER during Floral Initiation

Abstract: The transcription factors LEAFY (LFY) and APETALA1 (AP1), together with the AP1 paralog CAULIFLOWER (CAL), control the onset of flower development in a partially redundant manner. This redundancy is thought to be mediated, at least in part, through the regulation of a shared set of target genes. However, whether these genes are independently or cooperatively regulated by LFY and AP1/CAL is currently unknown. To better understand the regulatory relationship between LFY and AP1/CAL and to obtain deeper insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 47 publications
(87 reference statements)
6
68
0
Order By: Relevance
“…Although LFY alone is sufficient to activate AP1 78, 79 , accumulation of this floral commitment factor is delayed relative LFY activity. Under floral inductive conditions in inflorescences AP1 upregulation occurs two to three days after that of LFY 52, 80, 81 . The delay in AP1 upregulation is of biological significance as it enables formation of branches prior to the irreversible switch to flower fate 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Although LFY alone is sufficient to activate AP1 78, 79 , accumulation of this floral commitment factor is delayed relative LFY activity. Under floral inductive conditions in inflorescences AP1 upregulation occurs two to three days after that of LFY 52, 80, 81 . The delay in AP1 upregulation is of biological significance as it enables formation of branches prior to the irreversible switch to flower fate 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Other related MADS box proteins, such as CAULIFLOWER (CAL) and FRUITFULL (FUL) also promote determinacy (Ferrandiz et al 2000). In addition, consistent with its role in floral commitment, AP1 directly silences TFL1 with assistance from the SEPALLATA family transcription factor SEP4 (Ferrandiz et al 2000;Kaufmann et al 2010;Liu et al 2013;Serrano-Mislata et al 2016;Goslin et al 2017). Because of its role in the switch to reproductive development (inflores-cence formation), the role of FT in promoting floral fate is difficult to assess (Yamaguchi et al 2014).…”
Section: Axillary Meristems That Give Rise To Branches or Flowersmentioning
confidence: 95%
“…The onset of flower development in Arabidopsis is controlled by the interplay between LEAFY (LFY), APETALA1 (AP1) and its paralog CAULIFLOWER (CAL) [24]. We have already shown that garlic homolog of LFY (gaLFY) acts as a key-gene in the floral transition, as well as in inflorescence and flower differentiation [77].…”
Section: Gene Co-expressing During Meristem Transitionmentioning
confidence: 99%